Efektivitas Instrumen Asesmen Digital dalam Layanan Bimbingan dan Konseling: Sebuah Systematic Review - Elfi Churnia; Vasco Delano (Fakultas Ilmu Pendidikan Universitas Negeri Gorontalo, 2025)
This study aims to examine the effectiveness of digital assessment instruments used in guidance and counseling services across educational and mental health settings. A systematic review was conducted following the PRISMA 2020 guidelines, with searches performed across six major international databases. From a total of 1,264 identified articles, 20 met the inclusion criteria and were analyzed. The findings indicate that digital assessment instruments including web-based mental health screenings, mobile applications, and computer-based assessments generally demonstrate adequate to high validity and reliability. These instruments are effective for early detection, psychological monitoring, and supporting data-driven decision making in counseling services. Nevertheless, several challenges remain, including technological infrastructure limitations, varying levels of digital literacy among counselors, and concerns related to data security and privacy. Overall, digital assessments offer significant opportunities to enhance guidance and counseling services, provided that validated instruments are used and ethical data protection standards are upheld.